KONTRIBUSI MUHAMMADIYAH DALAM KAJIAN HADIS: ANALISIS MAJELIS TARJIH DAN METODOLOGI PENETAPAN HUKUM - Zulfahmi Alwi; M. Asyraf Mubarak Sudarmin, Muhammad Alwi Nasir (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2025)
Muhammadiyah is one of the largest Islamic organizations in Indonesia that plays an important role in advocating for Islam, particularly within Indonesia. The Muhammadiyah organization also focuses on Hadith and wields significant influence in Hadith studies in Indonesia, as evidenced by the decisions of Muhammadiyah's Tarjih Council, which is grounded in a paradigm based on the Quran and Sahih Hadith. This is because the name Muhammadiyah itself signifies an organization formed by followers of the Prophet Muhammad SAW, aiming to purify the teachings of monotheism within Indonesian society. This research employs a type of library research to analyze descriptive qualitative data utilizing the Hadith science approach. Consequently, this paper elucidates Muhammadiyah's contributions to the study of Hadith based on its Tarjih assembly. Within the Tarjih decisions, several determinations have been made, including the function of Hadith, the criteria for Hadith that can be used as evidence, establishing methods for resolving conflicting arguments, Ta'arudl al-Jarh wa al- Ta'dil, and Muhammadiyah's perspective on problematic Hadith (such as Dhaif Hadith, Mursal Hadith, Hadith narrated by Mudallis, and Ziyadah at-Tsiqah).